(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The institution of the precautionary principle in comparative law, background, basic elements in the doctrine, in a selection of international instruments and jurisprudential criteria of national courts of Mexico, France and Spain and international courts are analyzed in order to know the current scope. of the institution, reasoning used, fields of application (environment...) and dilemmas to protect human rights or international trade.